Pengaruh Budaya Masyarakat Tradisional dalam Rangka Penegakan Hukum Hak Kekayaan Intelektual (Lex Jurnalica, 2011)
When listening a song that remembering us in past fond memories, then at that time, we were actually listening to an intellectual work.. Certainly, few of us,  who want to know that he/she actually  created it, laboriously. When we saw a sign form of pictures, names, words that have been prepared on combination alluring colors, then at that moment, we were actually watching an intellectual masterpiece of the creator. Or when we eat fried chicken "Kentucky Fried Chicken" which is typical, accompanied by a question mark, wonderingly , how it made, then the answer is, it is a property right that guaranteed of its confidentiality. In addition to Intellectual Property Rights (IPR), such as: Industrial Design Patents, Layout Designs of Integrated Circuits (DTLST) and Plant Variety, all of which are protected by the state through legislation. Then,  question  arises, why they should be protected ?. Except, because Indonesia has ratified the international convention (treat), there are at least two (2) answers to that question. Firstly ,because Intellectual Property Rights               (IPR) exist  from a process of  thinking, laboriously, has to be appreciated. Then, secondly, Intellectual Property Rights (IPR) has economic value for their owners, directly and provide revenue for the state of the tax sector, indirectly. Among developed countries, Intellectual Property Rights (IPR)  have appreciation, respect and protection  and they become a serious concern, both state and among entrepreneurs. In the other side ,in developing countries just like Indonesia, recognition and protection of Intellectual Property Rights( IPR) are still very bad. Primarily among domestic entrepreneurs. Whereas ,the  owners of Intellectual Property Rights still have lower awareness of law to register their IPR to Directorate General of  Ministry of Law and Human Rights. It is highly influenced by the legal culture of society who do not really care or even to let his/her right imitated by person / other parties.Keywords: IPR Protection, Economic, Cultural Rights of the Public Law